(untitled) (Nepalese Journal of Management Research, 2023)
The main purpose of this research is to examine the impact of e-banking services on customer awareness of Nepalese commercial banks. To achieve the objective, descriptive as well as explanatory research designs were used. Primary data were collected from both questionnaires and interview that were distributed among the customers of all commercial banks. The descriptive result of the study indicates that the composite mean value of customer awareness is highest where as the mean value of reliability is the least. Similarly, the most consistent variable is privacy/security. The correlation analysis shows the positive and significant relationship among all dependent and independent variables. Furthermore, in terms of the values of the R square of the results of the regression, e-banking services such as accessibility, reliability, convenience and privacy/security explain 96% of variation on customer awareness. This study concludes that the convenience and privacy/security have significant positive effect on customer awareness of Nepalese commercial banks. More over the researcher recommend that the commercial banks should pay more attention to improve the overall level of customer awareness on accessibility and reliability.